"Where are all the Irish women engineers: a case study". Issue 25 (2019) - Kent, Mary Doyle; Costello, Orlagh; Kopacek, Peter
Abstract: In Ireland 2019 there is an obvious lack of female engineers in the workplace. This paper investigates the reasons why this is so and if gender diversity is needed in engineering? A qualitative and quantitative study was carried out and the results discussed. Comparison with international data is made and an analysis of the reasons behind the low figures is offered. Finally, potential solutions to attracting and keeping females engaged in engineering are proposed.